Investigate Efficiency & Reliability of Various Reprogramming Architectures for Wireless Sensor Network: A Survey - Gulhane, Veena; Malik, L.G. (International Journal of Sensors Wireless Communications and Control, 2012)
This paper presents a survey on the current state-of-art in various Reprogramming Architectures for Wireless Sensor Network (WSN). Recent research in wireless sensor network has highlighted the importance of supporting the capability for remote reprogramming of sensor nodes via wireless network. Wireless sensor networks are expected to be deployed for long periods of time, and the nodes are likely to need software update during their lifetime, both for bug fixes and in order to support new requirements. Network reprogramming allows for over-the-air software updates in sensor networks. Dynamic reprogramming of sensor applications and sensor operating systems are emerging as a critical function required in wireless sensor networks. This ability to remotely patch or upgrade software in deployed sensor nodes via the wireless network is complicated by the increasing trend towards heterogeneity in WSN hardware platforms, sensor operating systems and role-based differentiation, e.g. between aggregators and leaf sensor nodes. Most of the current network reprogramming protocols focus on propagating the same code image to a network of homogeneous sensor nodes. Naive approaches to adapt such protocols for heterogeneity are largely inefficient. Ease of programming has long been recognized as a major hurdle to the adoption of WSN technology. In response to this need, several platform dependent programming solutions have been hitherto developed. A well-established characterization of the available approaches is, however, largely missing. As a result, researchers are unable to orient themselves in this diverse field, and developers struggle in identifying the solutions most appropriate to their application requirements. The purpose of this survey is to describe features of different reprogramming architectures in wireless sensor networks & highlight major concerns pertaining to investigation of efficiency and performance of these architectures for Wireless Sensor Network. The modern techniques in various reprogramming architectures for WSNs have been examined in terms of Reprogramming Architecture, Code dissemination/Code acquisition, Encoding /Decoding, Single-hop/Multihop reprogramming, MAC protocol, Hierarchy, Pipelining, Scope Selection Support and Idle listening to adaptive sleeping etc. These features are surveyed for various Code dissemination protocols both Entire Program Image based & Difference-based Methods for reprogramming WSN.
Keywords: Dissemination protocols